Recoating Pada Lambung Single Mooring Buoy (Sbm) Milik Pt. Pelindo Iii - Budi Utomo, Samuel Febriary Khristyson (Politeknik Negeri Madura, 2019)
The SMB terminal is a facility that has dimensions in a small horizontal plane where a large size vessel is tethered and allows the vessel to rotate 3600 around its belay point. Thus, it can be said that many SMBs are located for offshore locations. As a supporting tool for ship navigation, the quality of SBM maintenance is needed, one of which is SBM hull painting. Protection against corrosion in SBM with the painting method and the stages in the painting, because almost all SBM constituent materials are metal, the protection of SBM bodies from corrosion by coating. The total area to be repainted is 40.87 m2, which is the largest in the SBM bottop area of 19.78 m2. Paint needs for 1 layer as much as 5 liters, equivalent to 1 can of size 5 liters per layer